OS01-12 A computational toolbox supporting the development of Safe and Sustainable by Design chemicals and materials - D. Sarigiannis; F. Nikiforou; A. Karakoltzidis; A. Agalliadou; T. Rydberg; M. Halling; C.L. Battistelli; E. Benfenati; C. Bossa; E. Bouman; É. Bourgé; M. Brouwer-Milovanovic; et al. (Toxicology Letters, 2024)

A revision of the Inocybe grammata group in North America including four new taxa - P. Brandon Matheny; Adriana Corrales; Mary Grace Graddy; Roy E. Halling; Jacob Kalichman; Linas V. Kudzma; Clark L. Ovrebo; Rachel A. Swenie; Noah C. Walker (Brittonia, 2022)

Different environmental variables predict distribution and cover of the introduced red seaweed Eucheuma denticulatum in two geographical locations - M. Eggertsen; S. A. Tano; D. H. Chacin; J. S. Eklöf; J. Larsson; C. Berkström; A. S. Buriyo; C. Halling (Biological Invasions, 2021)
In this study we examined abiotic and biotic factors that could potentially influence the presence of a non-indigenous seaweed, Eucheuma denticulatum, in two locations, one outside (Kane’ohe Bay, Hawai’i, USA) and one within (Mafia Island, Tanzania) its natural geographical range. We hypothesized that the availability of hard substrate and the amount of wave exposure would explain distribution patterns, and that higher abundance of herbivorous fishes in Tanzania would exert stronger top–down control than in Hawai’i. To address these hypotheses, we surveyed E. denticulatum in sites subjected to different environmental conditions and used generalized linear mixed models (GLMM) to identify predictors of E. denticulatum presence. We also estimated grazing intensity on E. denticulatum by surveying the type and the amount of grazing scars. Finally, we used molecular tools to distinguish between indigenous and non-indigenous strains of E. denticulatum on Mafia Island. In Kane’ohe Bay, the likelihood of finding E. denticulatum increased with wave exposure, whereas on Mafia Island, the likelihood increased with cover of coral rubble, and decreased with distance from areas of introduction (AOI), but this decrease was less pronounced in the presence of coral rubble. Grazing intensity was higher in Kane’ohe Bay than on Mafia Island. However, we still suggest that efforts to reduce non-indigenous E. denticulatum should include protection of important herbivores in both sites because of the high levels of grazing close to AOI. Moreover , we recommend that areas with hard substrate and high structural complexity should be avoided when farming non-indigenous strains of E. denticulatum .

Contrasting distribution and foraging patterns of herbivorous and detritivorous fishes across multiple habitats in a tropical seascape - M. Eggertsen; D. H. Chacin; C. Åkerlund; C. Halling; C. Berkström (Marine Biology, 2019)

Genotype introduction affects population composition of native Philippine Kappaphycus (Gigartinales, Rhodophyta) - Richard V. Dumilag; Ronelie C. Salvador; Christina Halling (Conservation Genetics Resources, 2016)

Extensive spread of farmed seaweeds causes a shift from native to non-native haplotypes in natural seaweed beds - S. A. Tano; C. Halling; E. Lind; A. Buriyo; S. A. Wikström (Marine Biology, 2015)

Introduction of Asian strains and low genetic variation in farmed seaweeds: indications for new management practices - Christina Halling; Sofia A. Wikström; Gustaf Lilliesköld-Sjöö; Erik Mörk; Elisabeth Lundsør; Giuseppe C. Zuccarello (Journal of Applied Phycology, 2013)

Linkage disequilibrium between the CYP2C19*17 allele and wildtype CYP2C8 and CYP2C9 alleles: identification of CYP2C haplotypes in healthy Nordic populations - Rasmus S. Pedersen; Charlotte Brasch-Andersen; Sarah C. Sim; Troels K. Bergmann; Jónrit Halling; Maria S. Petersen; Pál Weihe; Hege Edvardsen; Vessela N. Kristensen; Kim Brøsen; Magnus Ingelman-Sundberg (European Journal of Clinical Pharmacology, 2010)

Defensin Susceptibility and Colonization in the Mouse Model of AJ100, a Polymyxin B-Resistant, Brucella abortus RB51 Isolate - Shirley M. Halling; Allen E. Jensen; Steven C. Olsen (Current Microbiology, 2008)

Morphological and molecular evidence supporting an arbutoid mycorrhizal relationship in the Costa Ricanpáramo - Todd W. Osmundson; Roy E. Halling; Henk C. den Bakker (Mycorrhiza, 2007)

Comparison of Spore Inoculated and Vegetative Propagated Cultivation Methods of Gracilaria chilensis in an Integrated Seaweed and Fish Cage Culture - C. Halling; G. Aroca; M. Cifuentes; A. H. Buschmann; M. Troell (Aquaculture International, 2005)

Ecological engineering in aquaculture: use of seaweeds for removing nutrients from intensive mariculture - M. Troell; P. Rönnbäck; C. Halling; N. Kautsky; A. Buschmann (Journal of Applied Phycology, 1999)

Algal Toxicity of Antibacterial Agents Applied in Danish Fish Farming - H.-C. Holten Lützhøft; B. Halling-Sørensen; S. E. Jørgensen (Archives of Environmental Contamination and Toxicology, 1999)